2014
DOI: 10.1007/s00330-014-3554-6
|View full text |Cite
|
Sign up to set email alerts
|

Intravoxel incoherent motion diffusion-weighted imaging in the liver: comparison of mono-, bi- and tri-exponential modelling at 3.0-T

Abstract: • For normal liver, tri-exponential IVIM model might be superior to bi-exponential • A very fast compartment (D = 404.00 ± 43.7 × 10 (-3) mm (2) /s; f = 13.5 ± 0.8 %) is determined from the tri-exponential model • The compartment contributes to the IVIM signal only for b ≤ 15 s/mm(2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
135
1
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(148 citation statements)
references
References 38 publications
11
135
1
1
Order By: Relevance
“…tri-exponential function [23]. In addition, increasing data points in large b-values can influence the tissue diffusion coefficient, the kurtosis value obtained by DKI, and the α value obtained by the SEM.…”
Section: Discussionmentioning
confidence: 99%
“…tri-exponential function [23]. In addition, increasing data points in large b-values can influence the tissue diffusion coefficient, the kurtosis value obtained by DKI, and the α value obtained by the SEM.…”
Section: Discussionmentioning
confidence: 99%
“…Various fitting algorithms have been used to determine IVIM parameters, including asymptotic fitting (9)(10)(11)(12)(19)(20)(21)24,41,45,46,48,51,53), nonlinear least square (usually Levenberg-Marquardt) fitting (23,42,47,52,54,55), and Bayesian fitting (15,22,40,43,50). Current review cannot draw conclusion which one is better than others, nor can the mean values be compared (Figure 8).…”
Section: Image Post-processing Methods For Ivim Parametersmentioning
confidence: 99%
“…Different from asymptotic fitting that optimizes the measurement of Dslow, it gives an identical weight to each variable. However, it has been reported that leastsquares fitting has less stability compared to asymptotic fitting since it is sensitive to data outliers and image noise (38,48,53).…”
Section: Image Post-processing Methods For Ivim Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1988, Le Bihan et al 1 proved that, besides the water diffusion, a fast diffusion component existed in the brain. To deal with these problems, some other multiexponential IVIM models, such as the triexponential IVIM model 16 and the five-compartmental microcirculatory model, 17 were proposed by adding a number of perfusion components. In 1992, Neil et al 14 detected the multiexponential decay in 19F NMR experiments.…”
Section: Introductionmentioning
confidence: 99%